รูปแบบความสัมพันธ์ของปัจจัยการพัฒนาโรงเรียนทหารการสัตว์เป็นองค์การแห่งการเรียนรู้ - โหย่งไทย, มนัส; อินทร์รักษ์, ประเสริฐ (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อทราบ 1) ปัจจัยของการพัฒนาโรงเรียนทหารการสัตว์เป็นองค์การแห่งการเรียนรู้ 2) รูปแบบความสัมพันธ์ของปัจจัยการพัฒนาโรงเรียนทหารการสัตว์เป็นองค์การแห่งการเรียนรู้ 3) ผลการยืนยันรูปแบบ ความสัมพันธ์ของปัจจัยการพัฒนาโรงเรียนทหาร การสัตว์เป็นองค์การแห่งการเรียนรู้ กลุ่มตัวอย่าง ประกอบด้วย กำลังพล กรมการสัตว์ทหารบก จำนวน 331 นาย เครื่องมือที่ใช้ในการเก็บข้อมูลเป็นแบบวิเคราะห์เอกสาร แบบสัมภาษณ์มีโครงสร้าง และแบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ร้อยละ ค่ามัชฌิมเลขคณิต ค่าส่วนเบี่ยงเบนมาตรฐาน การวิเคราะห์ องค์ประกอบ การวิเคราะห์เส้นทาง และการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1) ปัจจัยของการพัฒนาโรงเรียนทหารการสัตว์เป็นองค์การแห่งการเรียนรู้ ประกอบด้วย ปัจจัยด้านผู้นำองค์การ ปัจจัยด้านวิสัยทัศน์ ปัจจัยด้านบุคลากร ปัจจัยด้านเทคโนโลยีสารสนเทศ ปัจจัยด้านโครงสร้างขององค์การ และปัจจัยด้านการเรียนรู้ร่วมกัน 2) ปัจจัยการพัฒนาโรงเรียนทหารการสัตว์เป็นองค์การแห่งการเรียนรู้ ทุกองค์ประกอบมีความสัมพันธ์กัน 3) รูปแบบความสัมพันธ์ของปัจจัยการพัฒนาโรงเรียนทหารการสัตว์เป็นองค์การแห่งการเรียนรู้มีความเหมาะสม ถูกต้อง เป็นไปได้ และสามารถนำไปใช้ประโยชน์ได้ สอดคล้องกับกรอบแนวคิดทฤษฎีของการวิจัย THE CORRELATIVE MODELS OF DEVELOPING FACTORS IN THE SCHOOL OF VETERINARY AND REMOUNT DEPARTMENT TO BE THE LEARNING ORGANIZATION The purposes of this research were to determine : 1) the developing factors in the schools of the veterinary and remount department to be the learning organization 2) the correlative models of developing factors in the schools of the veterinary and remount department to be the learning organization 3) the verification of the correlative models of developing factors in the schools of the veterinary and remount department to be the learning organization. The sample of this study were totally 331 respondents. The research instruments were the structured interview and the opinionnaires. The statistic used for analyzing the data were content analysis, frequency, percentage, mean, standard deviation, factor analysis and path analysis. The results of this research found that : 1) The developing factors in the schools of the veterinary and remount department to be the learning organization which comprise of 6 components were: leadership in organization, vision, personnel, information technology (IT), structured organization and shared learning. 2) The developing factors in the schools of the veterinary and remount department are correlate. 3) Verified that the correlative models of developing factors in the schools of the veterinary and remount department to be the learning organization were found appropriate, accurate, to be useful and accordance with the research conception framework.